PENERAPAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN AKUNTANSI PERUSAHAAN JASA DI SMK PASUNDAN 1 KOTA SERANG - Reni Febriani; Selvi Lucyana (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2018)
This study was aimed to find out how the application of Word Square learning model in class X SMK Pasundan 1 Serang City and to find out how the learning outcomes of students of class X SMK Pasundan 1 Serang City.This research used classroom action research method consisted of two cycles. Each cycle consists of four stages: planning, execution, observation and reflection. The subjects of this study were students of class X SMK Pasundan 1 Serang City consisted of 44 students and subject teachers as a team of collaborator.The results of this study indicated that the Word Square learning model could improve the student learning outcome because in the first cycle, there were 72.73% students who could reach score above KKM. While in the second cycle all students could reach score above KKM.